Towards equilibrium in income distribution: Theoretical background and empirical evidence for European countries - Friedrich L. Sell; Michael Öllinger (Universität der Bundeswehr München, Fachgruppe für Volkswirtschaftslehre, 2015)
The paper first aims at showing that personal income distribution - at least after government intervention - tends to be a stationary variable for many European countries. This finding backs earlier results achieved by Ramser (1987). Furthermore, personal incomes follow a log-normal distribution, regardless of time and location. The authors set up a theoretical equilibrium concept for personal income distribution which is located in status theory and which can explain why a certain or likewise 'optimal' degree of inequality is warranted in the society. In the empirical section of the paper, the authors present an in-depth analysis of personal income distribution (before and after government intervention) in 17 European countries (2004-2012). Linear regression exercises - which make use of Gini coefficients 'ex-ante' and Gini coefficients 'ex-post' - show that the total sample can be clustered into three subgroups. The main group of 10 countries (Germany, Czech Republic, Denmark, Finland, Belgium, Slovenia, Estonia, France, Luxembourg and Austria) seems to have already achieved equilibrium in income distribution. The other two, smaller groups (the so-called 'GIIPS': Greece, Ireland, Italy, Portugal, Spain on the one hand and Poland and Slovakia on the other hand) seem to be on the way to let their personal income distribution converge towards equilibrium, either 'from below' or 'from above'.
Keywords: D63; H23; O15; 330; Personal Income Distribution; Redistributive Policies; Globalization